2020
DOI: 10.1080/19490976.2020.1799533
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dairy and dairy derivatives on the gut microbiota: a systematic literature review

Abstract: The effects of dairy and dairy-derived products on the human gut microbiota remains understudied. A systematic literature search was conducted using Medline, CINAHL, Embase, Scopus, and PubMed databases with the aim of collating evidence on the intakes of all types of dairy and their effects on the gut microbiota in adults. Risk of bias was assessed using the Cochrane risk-of-bias tool. The search resulted in 6,592 studies, of which eight randomized controlled trials (RCTs) met predetermined eligibility criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 85 publications
(249 reference statements)
0
58
1
3
Order By: Relevance
“…Fifth, milk and dairy product consumption has been reported to affect gut microbiota, with favourable effects on beneficial genera (such as Lactobacillus and Bifidobacterium) and inhibition of pathogenic strains (such as Bacteroides fragilis) (Aslam et al 2020). Gut microbiota have been reported to play a role in systemic chronic inflammation, which has been established as a key factor for cardiovascular risk (Salvucci 2019).…”
Section: Editorialmentioning
confidence: 99%
“…Fifth, milk and dairy product consumption has been reported to affect gut microbiota, with favourable effects on beneficial genera (such as Lactobacillus and Bifidobacterium) and inhibition of pathogenic strains (such as Bacteroides fragilis) (Aslam et al 2020). Gut microbiota have been reported to play a role in systemic chronic inflammation, which has been established as a key factor for cardiovascular risk (Salvucci 2019).…”
Section: Editorialmentioning
confidence: 99%
“…In a preliminary study, Butler and co-authors observed that dietary changes based on the intake of dairy products promote the Lactobacillus abundance and suggest a link with the psychological status in participants by measuring the predictive neuroactive potential using a gut–brain module approach [ 12 ]. Accordingly, a recent survey indicated that the intake of dairy products such as milk, yogurt, and kefir may modulate the gut microbiota by increasing the Lactobacillus population [ 13 ], while consumption of a fermented dairy product containing a probiotic Lactobacillus casei strain reduces the duration of respiratory infections in the elderly [ 14 ]. However, the influence of dairy consumption in conjunction with other factors such as host genetics, age, sex, and lifestyle influences the gut microbiota composition and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, indoles (that are products of microbial tryptophan metabolism [6]) stimulate host intestinal mucin production, thereby providing an energy source to commensal bacteria and protecting the host intestinal layer from pathogen invasion [14]. Both LAB and metabolites derived from the fermentation process in dairy products thus have the potential to modulate the gut microbiota composition and mediate some of the health benefits of dairy products [15][16][17][18]. However, these effects are dependent on multiple factors including the metabolite flux across the digestive tract after dairy product consumption, the host microbiota composition, and the metabolic or health status of the consumer.…”
Section: Introductionmentioning
confidence: 99%